Assessing the play and learning environments of children under two years in peri-urban Lima, Peru: a formative research study - Jessica D. Rothstein; Audrey J. Buckland; Kristin Gagnier; Mayra Ochoa; Aliya Allen-Valley; Belinda Jivapong; Lilia Z. Cabrera; Elli Leontsini; Kelly R. Fisher (BMC, 2021)
Abstract Background Home-based interventions have potential for improving early child development (ECD) in low-resource settings. The design of locally acceptable strategies requires an in-depth understanding of the household context. In this formative research study, we aimed to characterize the home play and learning environments of children 6-23 months of age from low-income households in peri-urban Lima, Peru. Methods Drawing on the developmental niche framework, we used quantitative and qualitative methods to understand children's physical and social settings, childcare practices, and caregiver perspectives. We conducted interviews, unstructured video-recorded observations, and spot-checks with 30 randomly selected caregiver-child dyads, 10 from each child age group of 6-11, 12-17, and 18-23 months of age, as well as key informant interviews with 12 daycare instructors. We analyzed the data for key trends and themes using Stata and ATLAS.ti and employed an adapted version of the Indicator of Parent-Child Interaction to evaluate the observations. Results Children's social settings were characterized by multi-generational homes and the presence of siblings and cousins as play partners. Access to books and complex hand-eye coordination toys (e.g., puzzles, building blocks) in the home was limited (30.0 and 40.0%, respectively). Caregivers generally demonstrated low or inconsistent levels of interaction with their children; they rarely communicated using descriptive language or introduced novel, stimulating activities during play. Reading and telling stories to children were uncommon, yet 93.3% of caregivers reported singing to children daily. On average, caregivers ascribed a high learning value to reading books and playing with electronic toys (rated 9.7 and 9.1 out of 10, respectively), and perceived playing with everyday objects in the home as less beneficial (rated 6.8/10). Daycare instructors reinforced the problems posed by limited caregiver-child interaction and supported the use of songs for promoting ECD. Conclusions The features of the home learning environments highlighted here indicate several opportunities for intervention development to improve ECD. These include encouraging caregivers to communicate with children using full sentences and enhancing the use of everyday objects as toys. There is also great potential for leveraging song and music to encourage responsive caregiver-child interactions within the home setting.